ChemInform Abstract: A Simple Entry to Sugar Derived Bispiropyrrolidines Through Non‐Stabilized Azomethine Ylides. Issue 43 (7th October 2013) - Barman, Piyali Deb; Goyal, Divya; Daravath, Upendra Kumar; Sanyal, Ishita; Mandal, Sukhendu B.; Banerjee, Asish Kumar
Abstract Azomethine ylides, generated in situ from sarcosine, isatins, and cycloalkanones or acenaphthenedione, undergo 1, 3‐dipolar cycloaddition with the carbohydrate derived olefin (II) to afford the title compounds (IV) and (VI).